An overview of acute gastrointestinal side effects of systemic anti-cancer therapy and their management. (October 2020) - Smith, Padraic; Lavery, Anita; Turkington, Richard C.
Abstract: Treatment-related acute gastrointestinal toxicities are a common and often debilitating hurdle encountered in the treatment of cancer patients. While the introduction of targeted therapies such as tyrosine kinase inhibitors has led to improvements in survival outcomes, their use has also been complicated by a high frequency of clinically important adverse effects. Gastrointestinal toxicities such as nausea, vomiting, diarrhoea and hepatotoxicity represent potentially serious adverse events that may necessitate dose reductions, treatment interruptions and cessation of treatment. An improved knowledge of the incidence, pathophysiology, management and prophylaxis of these toxicities is crucial in order to reduce patient morbidity and mortality. In this review, we discuss the main gastrointestinal toxicities associated with chemotherapy and targeted therapies in oncology, outlining their incidence, pathophysiology and expert management guidelines.